Low-Temperature Mullite Formation in Ternary Oxide Coatings Deposited by ALD for High-Temperature Applications - Furlan, Kaline P.; Krekeler, Tobias; Ritter, Martin; Blick, Robert; Schneider, Gerold A.; Nielsch, Kornelius; Zierold, Robert; Janssen, Rolf (Advanced Materials Interfaces, 2017)
Atomic layer deposition (ALD) process presents thickness control in an Ångstrom scale due to its inherent surface self-limited reactions. In this work, an ALD super cycle approach, where a superposition of nanolaminates of SiO2 and Al2O3 is generated by cycling the precursors APTES–H2O–O3 and TMA–H2O, is used to deposit thin films with varying ratio of Al2O3:SiO2 into silicon wafers and into inverse photonic crystals. The resulting ternary oxide films deposited at low temperature (150 °C) are amorphous. However, conversion to mullite occurs at 1000 °C, way below the conversion temperatures found into powder processing or diphasic sol–gel routes (type II) and comparable to monophasic sol–gel synthesis. By means of such a mullite coating, the structural stability of an Al2O3 inverse photonic crystal is increased up to 1400 °C.
CRIS-Team Scopus Importer:2022-04-14
Keywords: atomic layer deposition; high-temperature applications; mullite; photonic crystals; thermal barrier coatings